2022
DOI: 10.1177/09544100211070868
|View full text |Cite
|
Sign up to set email alerts
|

Multi-objective surrogate model-based optimization of a small aircraft engine air-intake duct

Abstract: Aviation industry is constantly striving for more efficient design processes in respect to optimal time, human and computational resources utilization. This implies a need for application of an approximation techniques enabling for fast responses generation with maintained level of results quality. This study focuses on an advancement of aerodynamic shape optimization process of a small aircraft engine intake system by introduction of a surrogate modelling step into the design loop. The multi-objective metamod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…The study reported in [7] focused on improving the process of optimizing the aerodynamic shape of the small aircraft engine intake system. Optimization using a multicriterial model is carried out to reduce the loss of full pressure along the motor path and increase the uniformity of the flow in the plane at the inlet to the compressor.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…The study reported in [7] focused on improving the process of optimizing the aerodynamic shape of the small aircraft engine intake system. Optimization using a multicriterial model is carried out to reduce the loss of full pressure along the motor path and increase the uniformity of the flow in the plane at the inlet to the compressor.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…They can also prove more efficient and cost-effective when simulations demand high computational resources [6]. The application of metamodeling for optimizing air intake aerodynamics in jet engines has been explored in several studies, including the use of kriging models with efficient global optimization algorithms [10], [11], and multi-objective surrogate models [7].…”
Section: Introductionmentioning
confidence: 99%